Pharmacophore-based identification and in vitro validation of apoptosis inducers as anticancer agents. Issue 11 (1st November 2020) - Vyas, V.K.; Qureshi, G.; Dayani, H.; Jha, A.; Ghate, M.
ABSTRACT: Ligand-based pharmacophore modelling and virtual screening along with in vitro screening were performed as a rational strategy for the identification of novel compounds as apoptosis inducers and anticancer agents from the chemical database. Known apoptosis inducers were selected from the literature for generation of pharmacophore models, which were subjected to validation using Receiver operating characteristic (ROC) and Günere-Henry (GH) scoring methods. Based on highest fitness score of 4680.61, ROC value of 0.872 and GH score of 0.758, pharmacophore model-2 was selected as the best model. Model-2 as 3D search query was searched against the IBS database to find novel compounds as hits. Three hits were selected with a QFIT value more than 82 for in vitro screening as apoptosis inducers and anticancer agents. In vitro anticancer activity was performed using resazurin cell variability assay, and apoptosis inducing activity was determined using caspase-3 activation and annexin-FITC assays. One of the retrieved hit, STOCK5S-44056 demonstrated IC50 value of 23.56 µM in cell variability assay, and had EC50 value of 26.95 µM in caspase-3 activation assay. STOCK5S-44056 also indicated late stage induction of apoptosis in annexin assay. The results of in vitro activity revealed that STOCK5S-44056 has a potential to become anticancer agents.